A New Results of Injective Module with Divisible Property - Hammad, Fawzi N.; Abed, Majid Mohammed (Journal of physics. Conference series, 2021)
In this paper, we will present a new result that clarify the relationship between divisible module and Injective module. But before starting to give the most important results, we need to present the following lemma with some basic definitions that help us reach the desired goal.